15th International Conference "Intelligent Systems" (INTELS'22) - Diveev, Askhat; Zelinka, Ivan; Avetisyan, Arutun; Ilin, Alexander (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The 15th International Conference "Intelligent Systems - 2022" (INTELS'22) was held on 14-16 December 2023 at the Russian Academy of Sciences, Moscow, Russia. It is a biennial event with a thirty-year history. INTELS'22 focused on the areas of intelligent systems and artificial intelligence, their theoretical aspects, and their application to sustainable development. Most of the papers are devoted to research and development of control systems in robotics. Both classical methods and modern methods based on machine learning are used to solve complex control problems.